Intra‐familial health polarisation: how diverse health concerns become barriers to health behaviour change in families with preschool children and emerging obesity. Issue 6 (18th April 2020) - Hoeeg, Didde; Christensen, Ulla; Grabowski, Dan
Abstract: In a disadvantaged rural area in Denmark, severe challenges have been identified concerning overweight and obesity in families with preschool‐age children. The present paper examines how families with young children and emerging obesity issues perceive 'healthy living' and barriers to practising it. Using data from qualitative workshops with families and professionals working with them, we reveal health perceptions and related family dynamics. Drawing on P. Bourdieu's theory of habitus and 'tastes of necessity', K.L. Frohlich et al .'s notion of 'collective lifestyles' and E. Lindbladh and C. H. Lyttken's theory of preconditions for health behaviour change and reactions to risk‐related information, we analyse how risk perceptions and related health practices within the families are influenced by the local contexts in the disadvantaged area under study. Despite shared perceptions of 'healthy living', we found that diverse health‐risk perceptions created family dynamics in which parents performed opposed health behaviours, which became a huge barrier to becoming a healthier family. Based on our theoretical approach, we propose that risk perceptions and reactions are highly context dependent, as illustrated in both micro‐contexts (family dynamics) and the macro‐context (the disadvantaged area).